My Coney Island baby : a novel - O'Callaghan, Billy (HarperCollins, 2019)
"Radiant with beauty, longing, and desire, and deeply touching, this literary novel, reminiscent of the works of William Trevor and Colm Tóibín, evokes the long love affair between a man and a woman, each married to another, who meet every month in a decaying hotel in Coney Island, Brooklyn. These beautiful, carefully-rationed days have long sustained Michael and Caitlin's love, and have helped help them survive the tedium of their lives separate from each other. But now, amid the howling winds whipping off the Atlantic, and a snow storm blackening the horizon, this nearly abandoned resort feels like the edge of the world. On this winter day, burrowed in their private cocoon, they will discover that their lives are on the brink of change. Michael's wife is battling cancer, and Caitlin's husband is about to receive a major promotion, which will involve relocating to the Midwest. After half a lifetime together in their most intimate moments, certain long-denied facts must be faced, decisions made, consequences weighed and, maybe, just maybe, chances finally taken."--Amazon.